Effect of pulse-wave factors in Middle Aged Women by Mountain Cultivated Ginseng Pharmacopuncture Original Articles - Park Sang Wook; Kim Yi Soon; Hwang Won Deok; Kim Gyeong Cheol (Korean Pharmacopuncture Institute, 2011)
Objectives: The aim of this experiment is to know about Effect of pulse-wave factors in Middle Aged Women by Mountain Cultivated Ginseng Pharmacopuncture. Methods: First 20 Middle Aged women are diagnosed by pulse diagnosis, and then Mountain Cultivated Ginseng Pharmacopuncture(1 injection 20cc) were injected. 30 minutes later, pulse diagnosis again performed. As a result, method of one-group pretest-posttes design were used for evaluation. Results: T(Total pulse cycle) time statistically significant increased on both left and right chon, kwan,cheok. T4 time statistically significant increased on both left and right chon, kwan, cheok. T4-T1/T indexs except left cheokmaek, Right cheokmaek observation area decreased significantly in four sites.Wm(indicating high pressure retention time) indexs increased significantly in the five sites were observed except right chon maek. Conclusions: Effect of pulse-wave factors in Middle Aged Women by Mountain Cultivated Ginseng Pharmacopuncture increased T, T4, Wm and decreased T4-T1/T indexs. The results of this experiment,Mountain Cultivated Ginseng Pharmacopuncture induced to increase the Pulse-wave's stability and strength.